Entrepreneurship in Nepali Higher Education: An Interpretive Inquiry - Dhanapati Subedi (Foxton Books, 2019)
The purpose of this study was to explore how academic leaders of Nepali universities are experiencing entrepreneurship, changing contexts of higher education, and entrepreneurial activities to cope up with those changing contexts in order to lead universities. This inquiry is based on interpretive paradigm, which includes a multi-method approach. Five universities of Nepal were the researcher's living territories, where he interacted with nine participants in order to generate their narrative stories and experiences. The researcher explored and derived meanings from their stories and experiences, and in doing so, the researcher went through the process of coding, synthesizing, developing themes, analyzing, and interpreting meanings merging signature literature and theories of leadership and entrepreneurship. Through this enquiry, the researcher learned that entrepreneurship has multilayered meanings rooted in academic culture and society which could be understood being a part of the process. The researcher also learned that entrepreneurship is a process of dreaming and tracking a big picture, advocacy of change, elaboration of cognition, crossing the point of no return, a journey of togetherness, and tactful management of conflicts. The researcher also learned that changes in higher education in Nepal could be grouped under demand and supply market change. Within demand market, access, policy and awareness of parents and students are observed to have changed whereas within supply market, institutional providers, technology, pedagogy, curriculum and evaluation are found to have changed in higher education in Nepal. Apart from these, the researcher also learned that academic leaders of Nepali higher education have performed entrepreneurial activities like value added new programs, research and technological activities, fundraising activities, plan giving activities, retail sales and services, and real estate activities creating different values in order to cope up with those changing contexts in higher education. When the researcher examined the experiences and stories of the participants from leadership standpoint, he concludes that a vignette of entrepreneurship, changing context in higher education, and performance of entrepreneurial activities, have a nexus of dynamism in higher education.